Kanglei Haraoba-significance of its dances and nomenclature - Lourembam Turist Devi (International journal of economic perspectives, 2022)
Dance forms an inseparable part of human civilization since time immemorial. Dance can be defined as the act of portraying or expressing a certain particular part of historical events. Body movements, facial expression, costumes, instruments, taal, songs all constitute dance form. It is the basis of culture, custom and tradition of group of people living in different parts of the world. The Meitei community residing mainly in state of Manipur, north east India and some parts of countries like Myanmar, Bangladesh are culturally evolved, whose social life revolves around religious rites, dance, and music. For the Meiteis, dance and music have a strong connection to the ceremonial acts that occur throughout a person’s life